2011
DOI: 10.1177/1362361310387803
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into social information processing in young people with Asperger syndrome

Abstract: Deficits in social functioning are a core feature of autistic spectrum disorders (ASD), being linked to various cognitive and developmental factors, but there has been little attempt to draw on normative models of social cognition to understand social behaviour in ASD. The current study explored the utility of Crick and Dodge's (1994) information processing model to studying social cognition in ASD, and examined associations between social information processing patterns, theory of mind skills and social funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
4
26
0
1
Order By: Relevance
“…However, as a group, children with ASD showed a weaker preference for the pro‐social solution and more often than their TD peers favored responses reflecting not understanding or avoidance. That a greater than expected proportion of children with ASD chose avoidant responses is consistent with prior reports of children with ASD rating withdrawal from a situation as a favorable solution [e.g., Flood et al, ]. Children with ASD also demonstrated a more difficult time deciphering the problem, as demonstrated by higher than chance levels of choosing “don't know” for problem identification; this finding too is consistent with prior literature [e.g., Stichter et al, ; Bernard‐Opitz et al, ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, as a group, children with ASD showed a weaker preference for the pro‐social solution and more often than their TD peers favored responses reflecting not understanding or avoidance. That a greater than expected proportion of children with ASD chose avoidant responses is consistent with prior reports of children with ASD rating withdrawal from a situation as a favorable solution [e.g., Flood et al, ]. Children with ASD also demonstrated a more difficult time deciphering the problem, as demonstrated by higher than chance levels of choosing “don't know” for problem identification; this finding too is consistent with prior literature [e.g., Stichter et al, ; Bernard‐Opitz et al, ].…”
Section: Discussionsupporting
confidence: 88%
“…VESIP scores exhibited strong evidence of reliability. Consistent with prior studies using a range of assessment techniques [Channon et al, 2001;Bauminger et al, 2005;Embregts & van Nieuwenhuijzen, 2009;Flood et al, 2011;Meyer et al, 2006;Ziv et al, 2014;Russo-Ponsaran et al, 2015], children with ASD generally performed at a lower level than their TD peers. Response preferences varied significantly by diagnostic group.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Another recent study evaluated SIP and theory of mind skills in preschool‐aged children with autism [Ziv et al, ]. Contrary to Flood et al [], Ziv et al [] identified a positive relationship between better performance on false belief and knowledge access theory of mind tests and SIP steps of encoding and response generation within the ASD group. Differences in age range and specific diagnosis confound the comparison of results.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…This means that many universities are not ready yet for integration of students with AS, not only because of architectural access issues but also because of their current regulations and curricular and educational organization. Although great efforts are being made to continue with the required measures to support and advise students with AS, the consolidation of the principles of equality of opportunities and nondiscrimination in the university system is still far from meeting current regulations (Fleischer, 2012;Flood, Hare, & Wallis, 2011;Griffith, Totsika, Nash, & Hastings, 2012a;Griffith, Totsika, Nash, Jones, & Hastings, 2012b;Hughes, 2012;Ruiz, Pistrang, & Mandy, 2012;Sawyer, Williamson, & Young, 2012;Sciutto, Richwine, Mentrikoski, & Niedzwiecki, 2012;Shady, Luther, & Richman, 2013;Sharma, Woolfson, & Hunter, 2012;Swain, Nordness, & Leader-Janssen, 2012;Tolra´, 1998;Voss & Bufkin, 2011). To resolve these problems, it is necessary to move forward on the design, approval, and application of regulations, which assure an appropriate attention and support to students with AS, specifying quality standards and good practice indicators for an efficient functioning of support services to students in all different contexts and, by doing so, building continuity into academic and professional training (Alcantud, Á vila, & Asensi, 2000;Forteza & Ortego, 2003;Luque & Rodrı´guez, 2008) over the students' development.…”
Section: Introductionmentioning
confidence: 99%